God and moral law on the theistic explanation of morality - Murphy, Mark C. (Oxford : Oxford University Press, 2011)
Does God's existence make a difference to how we explain morality? Mark C. Murphy critiques the two dominant theistic accounts of morality - natural law theory and divine command theory - and presents a novel third view.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Christian ethics; Natural law -- Religious aspects -- Christianity; Divine commands (Ethics)